Assessing the accuracy of imputation in the gyr breed using different SNP panels - Toro Ospina, Alejandra Maria [UNESP]; Aguilar, Ignacio; Vargas de Oliveira, Matheus Henrique [UNESP]; Cruz Dos Santos Correia, Luiz Eduardo [UNESP]; Vercesi Filho, Anibal Eugênio; Albuquerque, Lucia Galvão [UNESP]; de Vasconcelos Silva, Josineudson Augusto [UNESP] (Canadian Science Publishing, 2021)
The aim of this study was to evaluate the accuracy of imputation in a Gyr population using two medium- density panels (Bos taurus - Bos indicus) and to test whether the inclusion of the Nellore breed increases the imputation accuracy in the Gyr population. The database consisted of 289 Gyr females from Brazil genotyped with the GGP Bovine LDv4 chip containing 30 000 SNPs and 158 Gyr females from Colombia genotyped with the GGP indicus chip containing 35 000 SNPs. A customized chip was created that contained the information of 9109 SNPs (9K) to test the imputation accuracy in Gyr populations; 604 Nellore animals with information of LD SNPs tested in the scenarios were included in the reference population. Four scenarios were tested: LD9K_30KGIR, LD9K_35INDGIR, LD9K_30KGIR_NEL, and LD9K_35INDGIR_NEL. Principal component analysis (PCA) was computed for the genomic matrix and sample-specific imputation accuracies were calculated using Pearson’s correlation (CS) and the concordance rate (CR) for imputed genotypes. The results of PCA of the Colombian and Brazilian Gyr populations demonstrated the genomic relationship between the two populations. The CS and CR ranged from 0.88 to 0.94 and from 0.93 to 0.96, respectively. Among the scenarios tested, the highest CS (0.94) was observed for the LD9K_30KGIR scenario. The present results highlight the importance of the choice of chip for imputation in the Gyr breed. However, the variation in SNPs may reduce the imputation accuracy even when the chip of the Bos indicus subspecies is used.
Keywords: Genomic analysis; Imputation accuracy; Tropical breeds